(untitled) (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Perception of users of the Brazilian National Health System (SUS) about the “Mais Médicos” (More Physicians) Program in a municipality in the countryside of Ceará, Brazil